An efficient approach to access 2,5-disubstituted 1,3,4-oxadiazoles by oxidation of 2-arenoxybenzaldehyde N-acyl hydrazones with molecular iodine - Başpınar Küçük, Hatice; Alhonaish, Anoud; Yıldız, Tülay; Güzel, Mustafa (Wiley-VCH Verlag, 2022)
An oxidative cyclization of 2-arenoxybenzaldehyde N-acyl hydrazones 3 a-o was employed to synthesize new 2,5-disubstituted 1,3,4-oxadiazole compounds 4 a-d, 4 f-i, 4 k-n. This method involves oxidative cyclization of 2-arenoxybenzaldehyde N-acyl hydrazones 3 a-o with molecular iodine mediated catalysis in which potassium carbonate served as a base. Characterization of all the synthesized novel compounds involved, proton and carbon NMR, mass spectrometry, and CHN elemental analysis. The synthesis of novel 2,5-disubstituted 1,3,4-oxadiazoles may display potential to provide pharmacologically important heterocyclic compounds.
Keywords: N-Acylhydrazones; Oxidative Cyclization; 1,3,4-Oxadiazoles; Molecular Iodine